Cord blood bilirubin used as an early predictor of hyperbilirubinemia - Ramamoorthy, Kannan; Abilash, M. S. (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal hyperbilirubinemia is among the commonest symptoms found in neonates. The information about risk of high bilirubin in infants allows simpler methods for reduction of bilirubin to be implemented before hyperbilirubinemia becomes significant and could help to take a decision for early discharge from Hospital. Thus, the authors were aimed at the assessment of the usefulness of the cord blood bilirubin as an early predictor of neonatal hyperbilirubinemia and the usefulness of 1st day bilirubin in predicting the neonatal hyperbilirubinemia. Methods: The present study was planned to conduct in Department of Pediatrics, Government Thiruvarur Medical College and Hospital, Thiruvarur among neonates delivered from 1st August 2011 to 1st December 2013. These neonates were followed from birth to 2nd postnatal day. Cord blood was collected at birth and bilirubin estimation was done within 12 hours of collection of the blood. Results: Cord blood bilirubin level of ≥2.15 mg/dl has a sensitivity of 73.08% and specificity of 59.49%, positive predictive value 14.6% and negative predictive value of 95.88% in predicting the risk of neonatal hyperbilirubinemia. 1st day bilirubin level of ≥5 mg/dl has a sensitivity of 92.3% and specificity of 71.16% and positive predictive value of 23.3% and negative predictive value of 98.9% in predicting the risk of neonatal hyperbilirubinemia. Conclusions: The use of the critical cord bilirubin level of 2 mg/dl in all healthy term newborns will predict significant hyperbilirubinemia.